Kindle fire HDX for dummies - Muir, Nancy C. (John Wiley & Sons, 2014)
Covers the Kindle Fire HDX and Kindle Fire HD tablets. Walks you through getting connected, navigating the touchscreen interface, working with Kindle Fire's built-in apps, using Amazon Cloud, and getting help from the Mayday feature. Helps you stay in touch with social media, e-mail, and Skype and find what you’re looking for online with Amazon’s Silk web browser. Shows you how to stay entertained with the latest apps, movies, TV shows, music, games, e-books, and other cool content for your Kindle Fire HDX or Kindle Fire HD